PEMBELAJARAN GITAR KLASIK DI YAMAHA MUSIC SQUARE (YMS) KOTA PONTIANAK - Ardiansyah, Rikky; Ghozali, Imam; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLearning was a process of someone to gain knowledge but, it required a stimulus that help in the process. The stimulus could be obtained from formal and non-formal type of education. Music course was one of non-formal typed of education which can improve student?s talents and skills in playing musical instruments, for example was Yamaha Music Square (YMS). Yamaha Music Square (YMS) had a unique characteristic in the curriculum of classical guitar learning so that was used to distinguish it from other courses. This study aim to describe the classical guitar leraning in Yamaha Music Square (YMS) Pontianak City. The subjects of this study was classical guitar teachers at YMS Pontianak. This research was focused on classical guitar learning at Yamaha Music Square (YMS) Pontianak City. The method used in this research was descriptive method and qualitative?s form research. Data obtained through observation, interviews, and documentation. The data validity technique was obtained through triangulation. The result showed that in learning classical guitar at YMS used a curriculum from Japan, otherwise known as an international curriculum with more attractive packaging. Learning methods used in classical guitar learning at YMS were interactive methods, demonstration methods, drill or drill methods and assignment methods. The material given in classical guitar learning at YMS is to recognize guitar parts, playing techniques for the right hand (apoyando and al-aire), finger numbers and symbols, tuning, melody exercise, scale C major and chord exercise. For the evaluation of classical guitar learning at YMS, each meeting was conducted through assignments given in the previous meeting and various events which are considered as benchmarks of student success. But the most important evaluation is that the test for grade upgrading is held twice a year. Keywords: yamaha music square, learning, classical guitar